Managing the smart revolution in travel, tourism, and hospitality - Sharma, Anukrati; Arora, Shruti; Sodani, Priya (Emerald Publishing Limited, 2025)
Managing the Smart Revolution in Travel, Tourism, and Hospitality provides a comprehensive exploration of how cutting-edge technologies are reshaping the landscape of the industry. Going beyond the surface of emerging trends, offering in-depth insights into the integration of smart technologies such as artificial intelligence, blockchain, and data analytics, chapters meticulously analyze their impact on operational efficiency, customer engagement, and overall management strategies within the realms of travel, tourism, and hospitality. From optimizing customer experiences to streamlining operational processes, the work serves as a vital guide, ensuring that stakeholders remain at the forefront of innovation, and capitalize on the opportunities presented by the rapidly evolving smart ecosystem in the constantly evolving hospitality sector. By elucidating the intricacies of this digital transformation, Managing the Smart Revolution in Travel, Tourism, and Hospitality equips industry professionals, academics and undergraduates with the knowledge and tools necessary to navigate the complexities of the smart revolution.
Includes index.
Keywords: Tourism -- Technological innovations.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality, sports, leisure and tourism industries.; elektronické knihy; electronic books